2014
DOI: 10.5194/cp-10-1817-2014
|View full text |Cite
|
Sign up to set email alerts
|

Coupled ice sheet–climate modeling under glacial and pre-industrial boundary conditions

Abstract: Abstract. In the standard Paleoclimate Modelling Intercomparison Project (PMIP) experiments, the Last Glacial Maximum (LGM) is modeled in quasi-equilibrium with atmosphere-ocean-vegetation general circulation models (AOVGCMs) with prescribed ice sheets. This can lead to inconsistencies between the modeled climate and ice sheets. One way to avoid this problem would be to model the ice sheets explicitly. Here, we present the first results from coupled ice sheet-climate simulations for the pre-industrial times an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 83 publications
(96 reference statements)
1
43
1
Order By: Relevance
“…The warming did not occur in simulations using the ICE-4G ice sheets (Justino et al, 2005;Kim, 2004) but it was present in simulations using the ICE-5G ice sheets (Pausata et al, 2011). Ziemen et al (2014) found that different ice-sheet configurations had a large impact on deep-water formation patterns in the North Atlantic and thus also on regional heat budgets and surface temperatures.…”
Section: Surface Temperaturementioning
confidence: 89%
“…The warming did not occur in simulations using the ICE-4G ice sheets (Justino et al, 2005;Kim, 2004) but it was present in simulations using the ICE-5G ice sheets (Pausata et al, 2011). Ziemen et al (2014) found that different ice-sheet configurations had a large impact on deep-water formation patterns in the North Atlantic and thus also on regional heat budgets and surface temperatures.…”
Section: Surface Temperaturementioning
confidence: 89%
“…The LGM uc ensemble accumulates ice in the North American part of the Bering Strait, whereas the ice in the LGM bs ensemble and ICE-5G reconstruction is in this part not that distinct. Ziemen et al (2014) attribute the overestimated accumulation in this region to the missing albedo variation in their model and moisture blocking of the atmospheric forcing. The land around the New Siberian Islands is covered by a small ice sheet in both ensembles, while this area is ice-free in the LGM ICE-5G reconstruction.…”
Section: Last Glacial Maximum Climate Forcing Model Tuningmentioning
confidence: 99%
“…The calibration and refining of Earth System models (ESM) to boundary conditions of past periods in the Quaternary is an ongoing effort to improve the predictive capabilities for future climate simulations (cf. Schmidt et al, 2014;Ziemen et al, 2014;Moberg et al, 2015). The integration of Quaternary proxy climatic data with ESMs on the global and the regional scale is needed to provide insight into non-linear response of climate dynamics on various spatial scales, for areas affected by monsoonal systems, and varying modes of ocean circulation, like the El Nino Southern Oscillation or the North Atlantic Oscillation.…”
Section: Interglacial Climate Variability and Mechanisms Of Climate Cmentioning
confidence: 99%